1998
DOI: 10.1046/j.1523-1747.1998.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Rat FGF-5 Protein in Skin Macrophage-like Cells and FGF-5S Protein in Hair Follicle: Possible Involvement of twoFgf-5 Gene Products in Hair Growth Cycle Regulation

Abstract: It has been reported that the gene for murine fibroblast growth factor-5 (Fgf-5) is expressed in the rat hair follicle and that this expression may be associated with catagen induction (Hebert et al, 1994). In this study, we analyzed the Fgf-5 gene product in skin because the gene generates two mRNA that translate into the FGF-5 protein and a short form of the FGF-5 protein (FGF-5S) as a result of an alternative splicing (Hattori et al, 1996; Ozawa et al, 1996). Indeed, we detected both types of FGF-5 mRNA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 47 publications
3
51
0
1
Order By: Relevance
“…Earlier studies have shown that FGF1, 2, 5, 7, 10, 13 and 22 are all highly expressed in the skin of C3H/HeN mice and that many of them play important roles in skin and/or hair dynamics (DuCros et al 1993, Hebert et al 1994, Danilenko et al 1995, Guo et al 1996, Rosenquist & Martin 1996, Mitsui et al 1997, Ortega et al 1998, Suzuki et al 1998, Nakatake et al 2001, Beyer et al 2003, Steiling & Werner 2003, Kawano et al 2004, 2005. Moreover, we have found that expression of these factors is strongly affected by the progress of the hair growth cycle (Kawano et al 2004(Kawano et al , 2005.…”
Section: Healing Of Excisional Full-thickness Skin Wounds In Young Anmentioning
confidence: 53%
“…Earlier studies have shown that FGF1, 2, 5, 7, 10, 13 and 22 are all highly expressed in the skin of C3H/HeN mice and that many of them play important roles in skin and/or hair dynamics (DuCros et al 1993, Hebert et al 1994, Danilenko et al 1995, Guo et al 1996, Rosenquist & Martin 1996, Mitsui et al 1997, Ortega et al 1998, Suzuki et al 1998, Nakatake et al 2001, Beyer et al 2003, Steiling & Werner 2003, Kawano et al 2004, 2005. Moreover, we have found that expression of these factors is strongly affected by the progress of the hair growth cycle (Kawano et al 2004(Kawano et al , 2005.…”
Section: Healing Of Excisional Full-thickness Skin Wounds In Young Anmentioning
confidence: 53%
“…However, recent studies have revealed significant information about possible regulatory factors of hair follicle catagen transformation. They include thyroid hormone and Vitamin D [4], hairless gene product [5], thrombospondin-1 [6], neurotrophin-3 [7], neurotrophin-4 [8], glial cell line-derived neurotrophic factor (GDNF) [9], fibroblast growth factor-5 (FGF-5) [10][11][12] and transforming growth factor-b1 (TGF-b1) [13]. These putative regulators have been extensively studied in mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…However, the origin of FGF5 has not been clearly established within mouse skin. One hypothesis is that FGF5 originating within the hair follicle outer root sheath acts to induce catagen (18), or alternatively, the source may reside in the follicle macroenvironment, potentially from FGF5-expressing macrophages that surround the hair follicle (19). To localize the isoforms of FGF5 in normal human hair follicles, we used PCR to amplify fragments of FGF5, and FGF5S in tissue from an unaffected individual, and found that both were expressed within occipital scalp skin in addition to plucked hair fibers (Fig.…”
Section: Identification Of Causative Mutations In Fibroblast Growth Fmentioning
confidence: 99%